Social Character in Politics of Nepali Communist Parties (Voice of History, 2023)
The paper analyses the social character in the politics of Nepali communists’ pastries particularly of the Nepal Communist Party (Unified Marxist and Leninist) and the Communist party of Nepal (Maoist Centre) by applying marxist perspective. It brings into light the essential causes and consequences of the rise and fall of communist movement in Nepal. The paper argues that every communist party has adopted appropriate social policies in their inception, but in course of their development, being deviated from their early stage became fascinated towards consumerist capitalist culture in their practical life. There are various reasons for this deviation. First, communist parties have failed to analyse the character of Nepali society properly as they have changed their analyses very often. Second, the leaders have been found double faced: they say one thing but do another as they are inherently guided by feudal psychology, comprador capitalist mentality and behaviour. Third, they have not been able to bring about socio-economic change as they have been engaged in the imbroglio of parliamentary politics. While trying to justify these issues, this paper incorporates the evidences from political documents and leaders’ statements. The paper is presented inductively and choice of methodology is qualitative.